MetastamiRs: A promising choice for antihepatocellular carcinoma nucleic acid drug development. Issue 1 (13th July 2016) - Wu, Liangcai; Bai, Xue; Xie, Yuan; Yang, Zhen; Yang, Xiaobo; Lin, Jianzhen; Zhu, Chengpei; Wang, Anqiang; Zhang, Haohai; Miao, Ruoyu; Wu, Yan; Robson, Simon C.; et al.
Abstract : Hepatocellular carcinoma (HCC) is the third leading cause of cancer mortality worldwide, which can be explained at least in part by its propensity towards metastasis and the limited efficacy of adjuvant therapy. MetastamiRs are miRNAs that promote or suppress migration and metastasis of cancer cells, and their functional status is significantly correlated with HCC prognosis. Unlike targeted therapy, metastamiRs have the potential to target multiple genes and signaling pathways and dramatically suppress cancer metastasis. In this review, we discuss the regulatory role of metastamiRs in the HCC invasion–metastasis cascade. Moreover, Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis has shown that many extensively studied metastamiRs target several critical signaling pathways and these have remarkable therapeutic potential in HCC. The information reviewed here may assist in further anti‐HCC miRNA drug screening and development.